Millennium Development Goals and the Poverty Question in Nigeria - Benedict, Akpomuvie Orhioghene (Mediterranean Journal of Social Sciences, 2011)
The paper examined the poverty question in Nigeria within the context of the Millennium Development Goals (NDGs),adopted by the United Nations in 2000. Over the past decades, Nigeria’s preoccupation with development has had very marginal success.The past failures and depressing prospects have provoked a great amount of concern. The paper revealed that most Nigerians are worse offthan they were; health and nutrition problems are widespread and infrastructure eroding rapidly. It further revealed that the achievementof the goal of stopping the traumatic march of poverty has so far eluded Nigeria and may not be able to achieve the ambitious MillenniumDevelopment Goal target of reducing poverty by half by 2015. The paper however, called for target policy interventions to protect the poorand a culture of prudent fiscal and monetary policy with incentives for non-oil growth and the development of the private sector.